Dynamics of spatial relationships among ecosystem services and their determinants: Implications for land use system reform in Northwestern China. (March 2021) - Lyu, Rongfang; Clarke, Keith C.; Zhang, Jianming; Feng, Junli; Jia, Xuehui; Li, Jijun
Highlights: Spatial relationships among five ecosystem services were quantified. Random forest analysis was used to identify their socio-ecological drivers. Topography plays an increasing role in sand fixation during 1989–2017. Socioeconomic development alters ecosystem service relationships. Land use pattern and vegetation coverage are critical in policy making. Abstract: Understanding the dynamics and relationships among ecosystem services (ESs) and their underlying socio-ecological driving mechanisms has great importance for policy-makers to achieve sustainable development. In this study, using the City Belt along the Yellow River in Ningxia, China as the study area, we quantified and mapped five ESs for the period 1989–2017, analyzed the spatial relationships among ESs through hotspots analysis, correlation analysis and cluster delineation, and explored the dynamic impacts of socio-ecological factors on ESs through random forest analysis. The results showed that spatial distributions and relationships among ESs had significant change over the past three decades, driven by the varied impacts of socio-ecological factors. Cropland in the central plain could supply higher values of food production, carbon sequestration and nutrient retention, which were mainly impacted by land use pattern and vegetation coverage and existed significant synergies among them at regional scale. Specially, the hotspots of food production and carbon sequestration both decreased in the northern part over time, while the former one was caused by the increasing impacts of socioeconomic indicators and the latter one by climate factors. Northwestern and southern mountains could provide higher values of sand fixation, which was mainly impacted by the increasing impact of topography and decreasing impact of climate factors. Thus hotspots of sand fixation increased in the mountainous areas and decreased in other regions. Socio-economic factors had an increasing impact on recreational opportunity, resulting the transformation of its hotspots from mountains to the central Yinchuan city and transition region between mountains and central plain. Dynamic impacts of socio-ecological factors could alter the spatial relationships among ESs and impact their co-occurrence across space. Specific management strategies have been proposed for different sub-regions to improve ESs under the land-use system reform, ecological civilization and rural revitalization in China.